Snap-Back Testing of Piles to Estimate Nonlinear Lateral Stiffeness and Damping Properties - Pender, M.J.; Beskhyroun, S; Norazzlina, M.Sa'don; Orense, R.P; Wotherspoon, L.M.; Arvanaghian, S.; Storie, L.B; Tidbury, M.D; Lambert, C.B. (2012)
The design of pile foundations likely to be subject to earthquake loading requires information about the nonlinear lateral load behaviour of the pile and also the damping properties during cyclic loading. We are researching methods for analysing the earthquake response of foundations that make use of Soil-Foundation-Structure-Interaction (SFSI) as a means of incorporating nonlinear soil deformation effects and nonlinear geometrical effects into the earthquake resistant design of foundations. There are three challenges in this work. First, to incorporate adequately the nonlinear response of the soil during the earthquake. Second, to account for geometrical nonlinearity during the earthquake - that is loss of contact between various parts of the foundation and the underlying and/or adjacent soil. Examples of this are the gapping that develops between a pile shaft and the surrounding soil during cyclic lateral loading and the uplift beneath parts of a shallow foundation subject to rocking. Third, to obtain appropriate values for the soil parameters which describe the nonlinear response of the foundations. The main thrust of this paper is to show how snap-back testing is an effective means of evaluating the cyclic behaviour of a pile foundation. An appealing feature of snap-back testing is that the pull-back part of the test gives data on the static nonlinear load deformation properties of the pile. This information is of use in push-over analyses which are often done as part of the design of piles subject to earthquake loading.